PENGARUH PENDIDIKAN KESEHATAN LATIHAN REHABILITASI JANTUNG TERHADAP PENGETAHUAN DAN KEMAMPUAN MOBILISASI DINI PADA PASIEN CONGESTIVE HEART FAILURE (CHF) - Elva ' Yenni; Sofiana ' Nurchayati; Febriana Sabrian ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2015)
Abstract The purpose of this research was to identify the effect of health education of cardiac rehabilitation exercise to knowledge and ability of early mobilization in patients with Congestive Heart Failure (CHF). This study used pra-experimental methods with pre and post-test without control. This research was conducted at Flamboyan ward Arifin Achmad Hospital Pekanbaru with 30 respondents.This research used purposive sampling technique. Measuring instrument of this research used questionnaire and observation sheet. The analysis used univariate and bivariate with using wilcoxon test. The results showed the effect of health education of cardiac rehabilitation exercise to knowledge with ρ value 0,004 and ability of early mobilization in patients with Congestive Heart Failure (CHF) with ρ value 0,000. It is  recommended to the hospital to include cardiac rehabilitation exercise program so that patients can do early mobilization activities within there capabilities for hospitalized Keywords: Ability, CHF, cardiac rehabilitation exercise, health education, and knowledge Bibliography: 42 (2000-2014)